Heterogeneous sonocatalytic activation of peroxomonosulphate in the presence of CoFe2O4/TiO2 nanocatalysts for the degradation of Acid Blue 113 in an aqueous environment. Issue 5 (October 2020) - S., Krishna; Sathishkumar, P.; N., Pugazhenthiran; Guesh, Kiros; Mangalaraja, R.V.; S., Kumaran; Gracia-Pinilla, M.A.; S., Anandan
Graphical Abstract: Highlights: Low-frequency ultrasound employed for nanocatalysts preparation and sonocatalysis. Increased d-spacing (1 0 1) perceived for TiO2 (0.35 nm) and CoFe2 O4 /TiO2 (0.38 nm). CoFe2 O4 /TiO2 /PMS/ultrasound endorsed 4-fold enhanced kinetics of AB113 degradation. 97% of AB113 mineralization has resulted from the sonocatalysis with PMS. CoFe2 O4 /TiO2 nanocatalysts reutilized up to six consecutive cycles. Abstract: CoFe2 O4 nanoparticles with band gap of 1.5 eV have excellent magnetic properties but poor catalytic degradation of Acid Blue (AB113) under ambient conditions due to the rapid recombination of electronic charges. To prevent the rapid recombination of electronic charges and to preserve magnetic properties exhibited by CoFe2 O4 nanoparticles, in this study a non-magnetic counterpart (TiO2 ) was engineered by low-frequency ultrasound (40 kHz) assisted processes. Properties of the materials were characterized using XRD, Raman, STEM-HAADF, VSM, and DR-UV-Vis analyses which confirms the lattice substitution of Ti 4+ by Co 2+ and Fe 3+ in the anatase crystal structure. TEM analysis reveals the enhanced d-spacing values for anatase (1 0 1) crystal plane when the value are compared for TiO2 (0.35 nm) and CoFe2 O4 /TiO2 (0.38 nm) which confirms the lattice substitution of Co 2+ and Fe 3+ and/or CoFe2 O4 nanocatalysts. The optical band gap was increased from 1.5 eV (CoFe2 O4 ) to 2.63 eV (CoFe2 O4 /TiO2 ). The magnetic nanocomposites demonstrated enhanced sonocatalytic rate (CoFe2 O4 /TiO2 = 6.026 × 10 -4 s -1 ) and (TiO2 = 2.135 × 10 -4 s -1 ) and magnetic properties. Heterogeneous sonocatalytic activation of peroxomonosulphate (PMS) validated ∼ 1.6-fold enhanced rate of mineralization of AB113 in the presence of CoFe2 O4 /TiO2 nanocatalysts. Besides, CoFe2 O4 /TiO2 nanocatalysts were found to be more stable during the re-utilization up to six consecutive cycles in the sonocatalytic processes. A suitable mechanism was proposed for sonocatalytic degradation of AB 113 in the presence of CoFe2 O4 /TiO2 magnetic nanocomposites.